(untitled) (World Bulletin of Public Health, 2025)
This article presents an analysis of scientific publications devoted to the problem of assessing the vitamin status of military personnel and methods for its elimination. It was found that professional athletes experience physical and psychological stress comparable to military personnel, and the need for vitamins is constantly increasing. The method of "megadoses", especially antioxidant vitamins, is not beneficial for health and endurance, but sometimes they have a pro-oxidant effect. The analysis reflects information that the correction of the vitamin status of the body should be carried out using a balanced diet (using traditional products), including products enriched with vitamins of mass consumption in the daily diet, the use of specialized (functional) products intended for certain categories of the population (military personnel serving in extreme and difficult climatic and geographical conditions), and vitamin-mineral complexes.